Extratropical cyclones over the southwestern South Atlantic Ocean: HadGEM2-ES and RegCM4 projections - Reboita, Michelle S.; da Rocha, Rosmeri P.; de Souza, Marcelo R.; Llopart, Marta [UNESP] (Wiley, 2018)
The value added from dynamic downscaling in climate projections of extratropical cyclones over the southwestern South Atlantic Ocean (SAO) is evaluated. For this purpose, the Regional Climate Model version 4 (RegCM4) is nested in the Hadley Global Environment Model 2 - Earth System (HadGEM2-ES) global climate model under the RCP8.5 scenario. The analyses focus on three time slices: the present (1979–2005), near future (NF: 2020–2050) and far future (FF: 2070–2098) climates. The cyclone tracking used an algorithm that searches for minima of relative vorticity at 925 hPa. Simulations of the present climate are compared to data from an ensemble of five reanalyses (ERA-40, ERA-Interim, NCEP-NCAR, NCEP-DOE and CFSR). For present climate, there is good agreement among reanalyses and models in associating austral winter and summer with higher and lower cyclone frequency, respectively. In addition, the simulations present the mean features of the cyclones (lifetime, distance travelled and mean velocity) as similar to those of the reanalysis. Moreover, RegCM4 outperforms the HadGEM2-ES by simulating more realistically the spatial pattern of the cyclogenesis density over the SAO, which indicates value added from the RegCM4 downscaling. For the future climates, a decrease is projected for the annual frequency of cyclones, which reaches −6.5% (−3.6%) in RegCM4 (HadGEM2-ES) in the NF and −11.4% (−10.4%) in the FF. Future projections do not indicate changes in the mean intensity of the cyclones. The negative trend of the cyclone frequency affects the precipitation. For FF, a decrease of approximately 15% in the precipitation associated with cyclones is projected.
Keywords: extratropical cyclones; future climate; HadGEM2-ES; precipitation; RegCM4; southwestern South Atlantic Ocean